Technology Adoption Among Government Employee in Semi-Rural Area, Sri Aman, Sarawak. - Benson Buda, Bennet Baja (Universiti Malaysia Sarawak (UNIMAS), 2021)
This study aims to identify the technology adoption trends among government employees in semi-rural area, Sri Aman, Sarawak. A survey methodology was used in this study. This research involves the utilization of questionnaire which was administered among 200 employees working in the selected government organization in Sri Aman. This study was conducted in 11 selected government organization in Sri Aman, Sarawak. The relationship between technology adoption and selected factors that influence technology adoption was analyzed using the Spearman Correlation Analysis. The dominant factor that affects technology adoption were identified using Multiple Regression analysis. The results revealed that there is a significant low relationship between ‘Access to technology’, ‘Internet availability’, and Device usage’ towards technology adoption meanwhile there is no significant relationship between ‘Ability to use internet’ and ‘Worker’s attitude and perception towards technology and internet’ towards technology adoption. The results also revealed that the dominant factor that affects technology adoption among government employee in Sri Aman is ‘Device Usage’. Hence, from this study, the organization can implement or modified current organizational strategies of implementing technology to improve the technology adoption among government employee in Sri Aman. In order to gain future insight regarding the area of this study, the future researcher can use other factor that can influence technology adoption in an organization as independent variables.